An assimilation of TRIZ in dissecting the statistical outcomes of tactile sensitivity, pinch force and endurance among elderly people. Issue 1 (1st January 2021) - Tan, Dominic Wen How; Ng, Poh Kiat; Noor, Ervina Efzan Mhd
Abstract: This study aims to examine tactile sensitivity effects on the pinch force and endurance of elderly people, and propose solutions extending from the statistical outcomes using the theory of inventive problem-solving (TRIZ). Pinch force and endurance time data were collected among 32 subjects aged 55–65 years according to a non-probability sampling method. Each participant received both treatments of increased and decreased tactile sensitivity through an experimental research design. Subjects pinched an experimental apparatus with different tactile sensitivities, and sustained their pinch for as long as possible. The results suggested that a significant difference existed between pinch force from reduced and increased tactile sensitivities, with similar outcomes for endurance. Resolving contradictions from the results led to the partial-action principle, which suggested that elderly people should pinch using less force when they lack the strength to achieve a certain force level, rather than exert a high force in a single attempt. The segmentation and other-way-around principles were also recommended. Su-Field analysis found that harmful effects from pinching can be neutralised using intermediary materials between the fingers and object, such as rubber. The analysis proposed using optical or acoustic fields, where light sensors or buzzers could act as mechanisms to signal users when sufficient force is achieved. These TRIZ-stimulated solutions provide new insights in resolving poor pinch performance caused by degrading tactile sensitivity.